SUBCUTANEOUS DIROFILARIASIS MASQUERADING AS LIPOMA/SCHWANNOMA - Dr. Jagriti Singh; Dr. Michelle Mathias; Dr Sajitha K (Tropical Journal of Pathology and Microbiology, 2024)
ABSTRACT An uncommon zoonotic illness called dirofilariasis is prevalent in tropical and subtropical regions of the world, including India. Canines are the principal hosts of the disease. Rarely humans get infected by the bite of mosquito which act as vectors to spread the infection. Pulmonary and extrapulmonary (orbital and subcutaneous) infections are commonly seen. Here we present 2 case reports in which patients presented with subcutaneous swellings. Excision biopsy was performed in both cases. Histopathological examination revealed Dirofilarial worm identified in the tissue sections with the characteristic morphologic features. Pathologists play a crucial part in the ultimate diagnosis. KEYWORDS: Dirofilaria repens, subcutaneous nodules, India, zoonotic infection